Paṇḍitarāja Jagannātha's Gaṅgālaharī : with the commentary by Śrī Sadāśiva & English translation - Jagannātha Paṇḍitarāja (Nag Publishers, 1999)
Classical verse work, with English translation and Pīyūṣalaharī commentary by Sadāśiva.